STUDENTS’ PERCEPTIONS ON USABILITY PRINCIPLE AND INTERFACE DESIGN OF FLIPBOOK AS M-LEARNING IN HIGHER EDUCATION - Novita Diana; Fauziah Fauziah; Farhana Sukhor (English Review: Journal of English Education, 2023)
This study aimed to determine the practicality of learning media developed by using flipbook applications and what students think about the use of e-module based on flipbook. Flipbook makes it easy to prepare e-modules that are more modern, creative, innovative and competitive. Flipbook is an application that can be used to create e-books, e-modules, e-papers, e-magazine. This application is very interesting because it can add sound, graphics, images, links and videos. This research is a design and product development research (Design and Development), used the Research and Development (R&D) method and analytical through a qualitative approach (Borg & Gall, 1983). Data collection in this study is the form of e-module validation and user responses in tertiary institutions. The validators in this study are linguists and media experts. The samples and data in this study were taken at one of the higher education in Aceh, namely Jabal Ghafur University. The development of this e-module allows users to learn independently because they can access it anytime and anywhere on mobile. The validation results of media experts stated that the aspects displayed in the e-module were very good. 66.7% stated that the e-module was appropriated to use without revision and 33.3% stated that it was appropriated to use with revision. The results of the students’ survey showed that 77.8% of the e-modules were feasible and practical to use in the learning process, and 22.2% stated that they were appropriated to use with revisions. The result shows that e-module based on Flipbook maker was good 4.44%, 52.23% said very good and 43.33% stated excellent. It mean that the e-module based on Flipbook will give a good impact on students learning.